Legal Protection of Consumers from Personal Data Security Risks, Threats of Fraud and Phishing (Cybercrime) in E-Wallet Payment Systems - Prayuti, Yuyut; Lany, Arman; Marpaung, Yohan Edward; Lorentzon, Elmend (Faculty of Law, University of Mataram, 2024)
In the era of financial technology, e-wallets have become a popular payment tool among e-commerce users aged 19-45. However, e-wallets face security issues, such as breach cases that harm users. Regulations such as PBI Number 20/6/PBI/2018 and POJK No. 6/POJK.07/2022 require organizers to ensure security and consumer protection, but their implementation is still in doubt. The purpose of this study is to analyze the legal protection of consumers from the risk of personal data security, the threat of fraud, and circumvention (cybercrime) in the e-wallet payment system. The method used in this research is normative research. Based on the principle of legality, cybercrimes such as data theft have violated the ITE Law, therefore a person's personal data must be protected according to the Ministry of Communication and Information and Bank Indonesia Regulations. According to Philipus M. Hadjon's theory of legal protection to overcome legal problems such as data theft on e-wallets, preventive and repressive measures are needed.